Are They Doing Enough for Their Goal? Exploration of Students' Readiness in Writing a Thesis - Asmiyah, Siti; Madjid, Hilda Izzati; Safriyani, Rizka (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
Students often consider writing a thesis project burdensome, resulting in longer completion of the degree. This article reports findings from a qualitative research exploring students' readiness to write bachelor theses. Questionnaires were distributed across different batches of students working on their thesis projects at an Islamic university in East Java. The respondents also participated in a focused discussion group to further explore their readiness. Data from 200 participants highlights that students generally have sufficient cognitive readiness regarding the areas and scopes of topics in ELT research. They have adequate to low academic readiness on aspects related to thesis writing as a form of academic writing. These students, however, have low social readiness. While the responses indicate that the students have high motivation to complete the thesis projects, more than half of the students reflected that they do not have a clear plan for the completion, are not very disciplined in working on their theses, have low reading interest and cannot manage their mood. The findings suggest that there is a gap between expectation and efforts. While they are cognitively ready, they are not socially ready. This implies that when supervising, the department and thesis supervisors need to touch upon psychological aspects of thesis writing intensively